Factors that Affect the Income Generation of Organic Rice Farmers in The Village of Pagung - Septian Maulana Purnama; Fadli Mulyadi; Jedda Ayu Inggrida; Edi Purwanto; Aulia Nadhirah; R Adharyan islamy (Jurnal Penelitian Pendidikan IPA, 2023)
Farmers in Indonesia generally have limited production factors, but on the other hand, they want to increase their farming business's production. This requires farmers to use their production factors efficiently. Efforts to increase farmer productivity and income are not easy because, in general, farmers in Indonesia have limited production factors and land. One measure that can make to meet this demand is to do farming, especially food crops, namely organic rice. Therefore, it is necessary to develop organic rice plants through the development of cultivation and application of technology, increasing business capital, investment, and product promotion facilities, as well as institutional facilities and partnerships between producers and business actors in organic rice production and marketing centers. The aims of this study were (1) to analyze the effectiveness of rice farming in Pagung Village and (2) to analyze the influence of production factors on land area, seeds, fertilizers, pesticides, and labor. This aim is expected to increase rice production and farmer income in Kepanjen District. The research used a sample of 80 rice farmers spread across Pagung Village, Semen District, Kediri Regency. The selection of respondents used the simple random sampling method because it is assumed that the population characteristics of each farmer were relatively homogeneous